Additional value of fetal magnetic resonance imaging in the prenatal diagnosis of central nervous system anomalies: a systematic review of the literature. (21st August 2014) - Rossi, A. C.; Prefumo, F.
ABSTRACT Objectives To analyze literature on the additional value of fetal magnetic resonance imaging (MRI) in assessing central nervous system (CNS) anomalies suspected by ultrasound. Methods A search was performed of PubMed, EMBASE, Cochrane library and the reference lists of identified articles. Inclusion criteria were CNS anomalies suspected/diagnosed by ultrasound, MRI performed after ultrasound, and postmortem examination by autopsy or postnatal assessment. MOOSE guidelines were followed. Outcomes assessed were positive/negative agreement between ultrasound and MRI, additional information provided by MRI, and discordance between ultrasound and MRI. Pooled sensitivity and specificity of MRI were calculated using the DerSimonian–Laird method. Postnatal/postmortem examinations were used as the reference standard. Results We identified thirteen articles which included 710 fetuses undergoing both ultrasound and MRI. MRI confirmed ultrasound‐positive findings in 65.4% of fetuses and provided additional information in 22.1%. MRI disclosed CNS anomalies in 18.4% of fetuses. In 2.0% of cases, ultrasound was more accurate than MRI. In 30% of fetuses, MRI was so different from ultrasound that the clinical management changed. Agreement was observed mainly for ventriculomegaly (51.3%). Disagreement was noted mainly for midline anomalies (48.6%). Pooled sensitivity of MRI was 97% (95% CI, 95–98%) and pooled specificity was 70% (95% CI, 58–81%). Conclusions MRI supplements the information provided by ultrasound. It should be considered in selected fetuses with CNS anomalies suspected on ultrasound. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.